Perancangan Interior Showroom Honda Surabaya Center - Marco Tanjaya; Stephanus P Honggowidjaja (Intra, 2018)
Along with the development of the times that occurred in Indonesia, the car that was once considered a luxury and only for certain circles only now turned into a means of transportation that is almost used and owned by all community groups. Therefore, many automotive brands are competing to offer their vehicle products with various advantages each and has a showroom facility along with a workshop that can accommodate both vehicle owners and potential buyers of vehicles. This is of course realized by the brand of Honda as one of the leading automotive brands from Japan which has a name that is well known in the community because of the car products offered a large power but still efficient. Honda has many showrooms scattered throughout Indonesia, one of which is Honda Surabaya Center located in the center of Surabaya that accommodate the public to be able to buy a car, setting up the car, to perform maintenance and service on the car owned. The purpose of this design is to create a showroom that can provide a new experience to visitors who come and staff and has a characteristic of Honda itself. The method used in this design process is design thinking are (1) Discovery, (2) Observe, (3) Emphatize, (4) Leverage Stories to Discover Insights, (5) Frame & Reframe, (6) Ideate, (7) Decide, (8) Prototype, (9) Validate Your Idea, (10) Iterate.